Drag Reduction of Crude Oil Flow in Pipelines Using Sodium Dodecyl Benzene Sulfonate Surfactant - A. R. Rassoul, G.; A. A. Hadi, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
In the present work, a closed loop circulation system consist of three testing sections was designed and constructed. The testing sections made from (3m) of commercial carbon steel pipe of diameters(5.08, 2.54 and 1.91 cm) . Anionic surfactant  (SDBS )with  concentrations  of (50,  100,  150, 200 and 250 ppm)  was tested as a drag reducing  agent.  The additive(SDBS)studied using crude oil from south of Iraq. The flow rates of crude oil were used in 5.08 and 2.54 cm I.D. pipes are (1 - 12) m3/hr while (1-6) m3/hr were used in 1.91 cm J .D. pipe . Percentage drag reduction (%Dr) was found to increase by increasing solution velocity, pipe diameter and additives concentration (i.e. increasing Renolds number). Also it was found that there is no change in apparent physical properties (viscosity) of crude oil after the addition of SDBS. The higher value of drag reduction of 54% in 5.08 cm I.D. was observed using 250 ppm SDBS surfactant dissolved in the used crude oil at flow  rate of 12 m3/hr. Friction factor  was calculated from  experimental data. The friction factors values for pure solvent lies near or at Blasius asymptote suggested for flow of Newtonian fluids. After the addition of small amount of SDBS, the friction factor values were positioned below Blasius asymptote toward Virk maximum drag reduction asymptote, which was never reached.